Assessment of Depression in Mothers of Children with Cerebral Palsy - Husnain Athar, Farrah Naz, Nayyab Tahir, Rameesha Omar, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Mothers of children with various degrees of impairment may bear a high amount of stress. Children with chronic medical disorders lead their moms to experience sadness, mental distress, and behavior problems. Aim: To determine the frequency of depression in mothers of children with cerebral palsy. Methodology: This cross sectional study was conducted in OPD of Neurology and Development Department, Children's Hospital Lahore in six months after the approval of synopsis August 20, 2020 till Feb 20, 2020. After taking written informed consent, 196 CP children's mothers were enrolled. Demographic information (including name, age) was also recorded. After admission to hospital detailed history and thorough clinical examinations were carried out to reach the provisional diagnosis. Results: The mean age of children was 6.65±2.23 years with age range of 3 and 10 years. There were 109(55.6%) male and 87(44.4%) female cases with higher male to female ratio. The mean age of mothers was 37.92±7.69 years with age range of 25 and 50 years. There were 115(58.7%) mothers who had depression and 81(41.3%) mothers did not have depression. There were 81(41.3%) mothers who had normal, 33(16.8%) had mild mood disturbance, 24(12.2%) mothers had borderline clinical depression, 23(11.7%) mothers had moderate depression and 35(17.9%) mother had severe depression. Practical implication: This study identifies a greater risk of depression in mothers of CP children, so by the help of this study we can identify such mothers at follow up of CP children and can give them psychiatric attention which can decrease mental health issues in them and would be beneficial for both the mother and their CP children. Conclusion: Depression among mothers of CP child was higher in this study, so these mothers must be given attention through psychiatric education and mental health programs to reduce their depression at the time of their CP children follow up. Keywords: Depression, care taker, disability, cerebral palsy, mental health